Al2O3–YAG:Ce composite phosphor ceramic: a thermally robust and efficient color converter for solid state laser lighting. Issue 37 (17th August 2016) - Li, Shuxing; Zhu, Qiangqiang; Tang, Daiming; Liu, Xuejian; Ouyang, George; Cao, Liangliang; Hirosaki, Naoto; Nishimura, Toshiyuki; Huang, Zhengren; Xie, Rong-Jun
Abstract : Al2 O3 –YAG:Ce phosphor ceramic shows excellent luminescence, thermal performance, and thus great suitability for use in solid-state laser lighting. Abstract : Solid state laser lighting is a newly emerging technology that combines a blue laser diode (LD) with a yellow-emitting phosphor converter to generate high-brightness white light. Due to high flux irradiation as well as thermal attack from the incident laser, this technology draws a demanding requirement on the thermal performance of the color converter. In this work, we design a Al2 O3 –YAG:Ce phosphor ceramic with a unique composite structure, where yellow-emitting YAG:Ce particles are embedded in a non-luminescent Al2 O3 matrix having high thermal conductivity. The large YAG:Ce particles (5–20 μm) show good crystallinity and a high external quantum efficiency of 76% (upon 460 nm excitation) while the fine Al2 O3 grains (0.5–2 μm) contribute to the superior in-line transmittance of 55% at 800 nm by minimizing the birefringence related scattering. The phosphor ceramic exhibits a high thermal conductivity of 18.5 W m −1 K −1 and a remarkable improvement in thermal stability (only an 8% reduction at 200 °C). When irradiated under 445 nm blue laser diodes, the phosphor ceramic shows no luminescence saturation even under a high power density of 50 W mm −2, validating its suitability for high-power solid state laser lighting.